Solo Exhibitions-Experimental Storytelling, Norrköping City Museum - Antoniou, Klitsa (My University, 2026)
Solo Exhibitions-In the Frame of Orphaned Images Exhibition Organized by Norrkoping Air, affiliated with Linkoping university and the Museum of Forgetting, Sweden Sweden